2017
DOI: 10.1101/166355
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Use of a Sibling Subtraction Method (SSM) for Identifying Causal Mutations inC. elegansby Whole-Genome Sequencing

Abstract: (250 words)Whole-genome sequencing (WGS) has become an indispensible tool for identifying causal mutations obtained from genetic screens. To reduce the number of causal mutation candidates typically uncovered by WGS, C. elegans researchers have developed several strategies. One involves crossing N2-background mutants to the polymorphic strain CB4856, which can be used to simultaneously identify mutant-strain variants and obtain high-density mapping information.This approach, however, is not well suited for unc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Complementation analysis indicated that mib41 and mib42 affect two independent loci. We determined the genomic regions of interest by single nucleotide polymorphism (SNP) mapping (Davis et al, 2005), and identified candidate causative mutations using the sibling subtraction method for mapping by whole-genome sequencing (Joseph et al, 2018). We obtained a single cluster of candidate mutations for each mutant allele on opposite arms of the X chromosome, consistent with the SNP mapping data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complementation analysis indicated that mib41 and mib42 affect two independent loci. We determined the genomic regions of interest by single nucleotide polymorphism (SNP) mapping (Davis et al, 2005), and identified candidate causative mutations using the sibling subtraction method for mapping by whole-genome sequencing (Joseph et al, 2018). We obtained a single cluster of candidate mutations for each mutant allele on opposite arms of the X chromosome, consistent with the SNP mapping data.…”
Section: Resultsmentioning
confidence: 99%
“…We used the sibling subtraction method to identify the causative mib41 and mib42 mutations by whole-genome sequencing (WGS) (Joseph et al, 2018). From heterozygous erm-1::GFP/+; mib41/+ or erm-1::GFP/+; mib42/+ hermaphrodites we isolated homozygous mib41 or mib42 mutant, homozygous nonmutant, or heterozygous F2 progeny.…”
Section: Methodsmentioning
confidence: 99%
“…Complementation analysis indicated that mib41 and mib42 affect different loci. Through single-nucleotide polymorphism mapping and whole-genome sequencing, 22,23 we identified a single cluster of candidate mutations for each allele.…”
Section: Loss Of Bbln-1 Causes Cytoplasmic Invaginations Of the Intestinal Apical Membranementioning
confidence: 99%
“…We used the sibling subtraction method to identify the causative mib41 and mib42 mutations by whole-genome sequencing (WGS). 23 From heterozygous erm-1::GFP/+; mib41/+ or erm-1::GFP/+; mib42/+ hermaphrodites we isolated homozygous mib41 or mib42 mutant, homozygous nonmutant, or heterozygous F2 progeny. Genomic DNA was then purified from pooled F3 progeny derived from 12-16 F2 animals and sequenced on an Illumina HiSeq X Ten platform.…”
Section: Identification Of Mib41 and Mib42 Mutationsmentioning
confidence: 99%
“…147 148 Nonsense mutation in elpc-2 causes progressive loss of adult locomotor function in 149 ix243 worms 150 We used whole genome sequencing and a modified version of the sibling 151 subtraction method to identify the causative mutation site in the ix243 strain ( Fig. S5) 152 (Joseph et al, 2018). Mutations were evenly induced on all chromosomes in the ix243 153 mutant strain before backcrossing ( Fig.…”
Section: Introduction 31mentioning
confidence: 99%